2017
DOI: 10.11646/zootaxa.4258.2.2
|View full text |Cite
|
Sign up to set email alerts
|

Revision of Disphaerobius Attems, 1926 (Chilopoda: Lithobiomorpha: Lithobiidae: Pterygoterginae), a centipede genus with remarkable sexual dimorphism

Abstract: Disphaerobius Attems, 1926, the sole constituent genus of the subfamily Pterygoterginae, is synonymized with Pterygotergum Verhoeff, 1934 syn. nov., and is shown to comprise only two species: D. svenhedini (Verhoeff, 1934) comb. nov. ex Pterygotergum, and D. loricatus (Sseliwanoff, 1881) (= Lithobius magnificus Trotzina, 1895), both syn. nov. and comb. nov. ex Lithobius Leach, 1814. Disphaerobius is rediagnosed, both of its basically Central Asian species are redescribed from fresh material of both sexes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 532 publications
(15 citation statements)
references
References 9 publications
2
13
0
Order By: Relevance
“…Based on a number of striking similarities in the peristomatic structures, Ganske et al () inferred a close relationship between the genus Disphaerobius (= Pterygotergum ), on which the subfamily Pterygoterginae Verhoeff, 1933, is based, and the lithobiine (sub)genera Lithobius and Ezembius . These similarities are congruent with other shared characters from external morphology identified in a recent taxonomic work (Farzalieva et al, ). Here, we further compared the mandibular gnathal edge of Disphaerobius loricatus , Hessebius plumatus (Zalesskaja, ) and Lithobius ( Ezembius ) giganteus and noted strong similarities, especially in the presence of simple spines on the internal side; the low number of simple, triangular accessory denticles; and the similar pattern of the fringing bristles, these branching distally only and showing broad bases.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Based on a number of striking similarities in the peristomatic structures, Ganske et al () inferred a close relationship between the genus Disphaerobius (= Pterygotergum ), on which the subfamily Pterygoterginae Verhoeff, 1933, is based, and the lithobiine (sub)genera Lithobius and Ezembius . These similarities are congruent with other shared characters from external morphology identified in a recent taxonomic work (Farzalieva et al, ). Here, we further compared the mandibular gnathal edge of Disphaerobius loricatus , Hessebius plumatus (Zalesskaja, ) and Lithobius ( Ezembius ) giganteus and noted strong similarities, especially in the presence of simple spines on the internal side; the low number of simple, triangular accessory denticles; and the similar pattern of the fringing bristles, these branching distally only and showing broad bases.…”
Section: Discussionsupporting
confidence: 90%
“…Phylogenetic analyses using maximum parsimony and maximum likelihood of the newly described characters together with characters from other morphological systems were performed, including characters extracted from other Lithobiidae, Henicopidae, and two representatives of Scutigeromorpha as outgroup. We further compared the mandibular gnathal edge of Disphaerobius loricatus (Sseliwanoff, ) and Lithobius ( Ezembius ) giganteus Sseliwanoff, and, together with the phylogenetic results, verified that it supports previous suggestions on their relationships based on external morphological and peristomatic characters (Farzalieva, Nefediev, & Tuf, ; Ganske et al, ). This is of particular systematic importance because Disphaerobius is usually classified separately from Lithobius , in the subfamilies Pterygoterginae and Lithobiinae, respectively.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…Six species are known from Xinjiang (China) (Ma et al, 2014) and 15 species from Altai Republic in Russia (Zalesskaja, 1978;Nefediev et al, 2016Nefediev et al, , 2017a. Ten species of centipedes are known from the best studied northern part of Mongolia (Poloczek et al, 2016), while only six species have been reported from western part of country, namely Disphaerobius svenhedini (Verhoeff, 1934) Loksa, 1978, Hessebius styliferus (Loksa, 1978) and Schizotergitius altajicus Loksa, 1978(Loksa, 1965Farzalieva et al, 2017). This paper is based on the material collected by A.A. DISTRIBUTION.…”
mentioning
confidence: 99%